Systematic review and meta-analysis on the associations of polypharmacy and potentially inappropriate medication with adverse outcomes in older cancer patients - Chen, Li-Ju; Trares, Kira; Laetsch, Dana Clarissa; Nguyen, Thi Ngoc Mai; Brenner, Hermann; Schöttker, Ben (The journals of gerontology. Series A, Biological sciences, medical sciences, 2020)
Both polypharmacy and potentially inappropriate medication (PIM) intake are highly prevailing in older cancer patients. However, only studies on the association of polypharmacy and postoperative complications have been meta-analyzed previously. A systematic review and a meta-analysis of prospective/retrospective observational studies reporting associations of polypharmacy or PIM with at least one out of five predefined adverse health outcomes in a population of older cancer patients (≥60 years) were carried out.
Gesehen am 14.09.2022